2018
DOI: 10.2214/ajr.17.19276
|View full text |Cite
|
Sign up to set email alerts
|

Can Adrenal Adenomas Be Differentiated From Adrenal Metastases at Single-Phase Contrast-Enhanced CT?

Abstract: Adrenal metastases cannot be reliably differentiated from adenomas at single-phase contrast-enhanced CT. Increased tumor size and heterogeneity were specific findings but showed unacceptably low sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 51 publications
4
14
0
1
Order By: Relevance
“…In our study, T2-weighted SI was also significantly lower in lipid-poor adenomas compared with a large group of adrenal metastases from various primary malignancies using both subjective and quantitative assessment with a five-point Likert scale and through the measurement of a simple T2weighted SI ratio. The use of texture analysis in adrenal assessment has been predominantly applied in CT, with few studies evaluating texture features of adrenal masses on MR images (24,(45)(46)(47)(48)(49)(50). In our study, both qualitative and quantitative analyses of tumor heterogeneity revealed that metastases were significantly more heterogeneous compared with lipid-poor adenomas, which is comparable to a prior study which compared adrenal metastases from renal cell carcinoma and adenomas at T2-weighted MRI (21).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In our study, T2-weighted SI was also significantly lower in lipid-poor adenomas compared with a large group of adrenal metastases from various primary malignancies using both subjective and quantitative assessment with a five-point Likert scale and through the measurement of a simple T2weighted SI ratio. The use of texture analysis in adrenal assessment has been predominantly applied in CT, with few studies evaluating texture features of adrenal masses on MR images (24,(45)(46)(47)(48)(49)(50). In our study, both qualitative and quantitative analyses of tumor heterogeneity revealed that metastases were significantly more heterogeneous compared with lipid-poor adenomas, which is comparable to a prior study which compared adrenal metastases from renal cell carcinoma and adenomas at T2-weighted MRI (21).…”
Section: Discussionsupporting
confidence: 81%
“…T2-weighted SI and heterogeneity may be very useful in cases of renal cell carcinoma and hepatocellular carcinomas, as metastases may show microscopic fat simulating lipid-rich adenomas at chemical shift MRI (8,51) and because both tumors are hypervascular and may wash out into the adenoma range at washout CT examinations (52). When using CT, tumor heterogeneity has been found to be a consistently useful feature, with metastases demonstrating increased heterogeneity compared with adenomas (24,45). In a study examining the apparent diffusion coefficient histogram analysis in adrenal nodules, heterogeneity was found to be significantly lower for adenomas compared with pheochromocytomas (48).…”
Section: Discussionmentioning
confidence: 99%
“…CT attenuation value (Tu et al 2018), rim enhancement and the presence of irregular margins were not found to differentiate significantly between adenomas and malignant lesions (Tu et al 2018). However, adenomas exhibit less than 10 Hounsfield Units (HU) on the unenhanced CT or show significant contrast washout (>60% absolute washout or >40% relative washout) (Park et al 2012, Wale et al 2017, Tu et al 2018. On MRI, adenomas exhibit high intracellular lipid content with a chemical-shift index greater than 15% (McCarthy et al 2016) (Fig.…”
Section: Imagingmentioning
confidence: 99%
“…The radiological distinction of adrenal metastases from an adenoma on CT imaging is based on tumour size and heterogeneity, these features exhibiting high specificity but low sensitivity. CT attenuation value (Tu et al 2018), rim enhancement and the presence of irregular margins were not found to differentiate significantly between adenomas and malignant lesions (Tu et al 2018). However, adenomas exhibit less than 10 Hounsfield Units (HU) on the unenhanced CT or show significant contrast washout (>60% absolute washout or >40% relative washout) (Park et al 2012, Wale et al 2017, Tu et al 2018.…”
Section: Imagingmentioning
confidence: 99%
“…Concerning adrenal lesions, CTTA has shown some promise in differentiating malignant from benign lesions. However, external validity of the findings in relation to lung cancer is hampered by small samples, single-center design, or non-lung cancer population [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%